Managing Performance: Digitalization as Strategy - Denisa ILIESCU; Cezar SCARLAT (Communications of International Proceedings, 2021)
The performance subject is an actual one, which has attracted the interest of the academic society and situates itself in the attention of the corporate representatives. Besides its complexity, managing performance is imperative in the present business constant changing environment and today’s turbulent times. Assessment methods adapted to the particularities of the companies ensure superior results and a greater flexibility. By quantifying the efficiency and effectiveness, best actions can be taken in order to achieve the accomplishment of objectives and even exceedance of expectations, well desired by the competitive and limited resourced environment. Accelerated digitalization leads to superior results and an increased achievement potential. The triadic model of digitalization is presented. Current study comes with contribution to both the performance literature and to practicing professionals with the latest concepts necessary for a high performance and beyond.
Keywords: Performance; Performance management; Digital technologies; Digitalization strategy; Triadic models; Triple S holistic approach